13 Pittori a Roma. - Balestrini, Nanni; Dorfles, Gillo; Eco, Umberto; Giuliani, Alfredo; Pagliarani, Elio; Porta, Antonio; Sanguineti, Edoardo; Vivaldi, Cesare (Roma : Galleria La Tartaruga, 1963)
Angeli, Franco ; Bignardi, Umberto ; Festa, Tano ; Fioroni, Giosetta ; Kounellis, Jannis ; Mambor, Renato ; Mauri, Fabio ; Novelli, Gastone ; Perilli, Achille ; Rotella, Mimmo ; Saul, Peter ; Tacchi, Cesare ; Twombly, Cy
13 Pittori a Roma, Galleria La Tartaruga, Roma, 9 febbraio 1963
boek